THE MILLENNIAL GENERATION IN TRANSFORMATION RELIGIOUS TOURISM - Zuhri , Saifuddin (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of this study is to define/explain the transformation of the millennial generation towards religious tourism. This research is a library research The results of this study explain the concept of the participation of the millennial generation in the transformation of religious tourism which has provided insight into how an organization must and can manage its potential human resources that can advance the region through the tourism sector.